DUKUNGAN SOSIAL TEMAN SEBAYA DAN RELIGIUSITAS: STUDI PSYCHOLOGICAL WELL-BEING PADA TARUNA TINGKAT II AAL - Ilham Akbar Feriananto; Dewi Mustami’ah; Puri Aquarisnawati (Fakultas Psikologi Universitas Hang Tuah, 2021)
This study aims to determine the relationship between peer social support and religiosity with psychological well-being in AAL level II cadets independently and simultaneously. The number of respondents was 100 AAL Cadets Level II students taken by saturated sampling technique. The results showed that there was a simultaneous relationship between peer social support and religiosity with psychological well-being. The findings also show that peer social support and religiosity show a positive relationship towards psychological well-being.